The Impact of the Global Crisis of 2008-09 on the Relationship Between Stock Markets and Oil Prices in the BRIC Countries - Gozgor, Giray; Natanelov, Valéri; Van Huylenbroeck, Guido (Indian Journal of Finance, 2015)
This paper examined the relationship between the equity indices in the BRIC economies and oil prices for the period from September 22, 1997 to November 29, 2013. We focused on various sub-periods to obtain statistically robust and economically solid relationships and to address cross-sectional dependence among stock market indices and oil prices in panel data techniques. For this purpose, we developed a test framework that made use, in a sequential order, of the second generation panel unit root test, the panel cointegration technique accounting for multiple structural breaks, the panel-Granger causality test, and the panel dynamic ordinary least square estimations to analyze the possible interactions. The results showed that there is a long-run positive relationship between the stock market indices and the oil prices only after fall 2008 in the panel framework. We analyzed the related period for each country in detail, and found that oil prices have positive effects on the equity indices in Russia, China, and India. Our findings also indicated that there is a causality relationship that runs from the oil prices to the stock markets’ indices in China and India, and there is a pair-wise causality between the equity indices and the oil prices in the Russian economy.